Effect of thermal conductivities of shape stabilized PCM on under-floor heating system. (15th April 2015) - Cheng, Wenlong; Xie, Biao; Zhang, Rongming; Xu, Zhiming; Xia, Yuting
Highlights: HCE-SSPCM was prepared and used in under-floor heating system. Enhancing thermal conductivity improved the efficiency of energy and space. Too high thermal conductivity over a range was meaningless. The economic benefits of the phase change energy storage system were the best. Abstract: A kind of heat conduction-enhanced shape-stabilized PCM (HCE-SSPCM) was utilized in the under-floor heating system for house heating in winter. This system charges heat by using cheap nighttime electricity and provides heating needs throughout all day. The effect of thermal conductivity of the PCM on energy savings and economic benefits of the system were theoretically and experimentally studied. HCE-SSPCM plates, made of (solid paraffin + liquid paraffin)/high density polyethylene/expanded graphite, were introduced to a test room with under-floor heating system. And the operating characteristics of the system were compared with that of the non-phase change energy storage system and the conventional air conditioning system. The results showed that enhancing the thermal conductivity of PCM in a certain range could significantly improve the energy efficiency of the heating system and reduce the thickness of thermal insulating materials. But the improving effect was not obvious when the thermal conductivity was beyond 1.0 W/m K. The phase change energy storage system had a comfortable temperature environment and the best economic benefits among the three different heating types especially when the ratio of peak-valley electric price was high. Therefore, increasing the thermal conductivity of SSPCM will be of great significance for house heating.